Evaluation of nuclear chromatin using grayscale intensity and thresholded percentage area in liquid‐based cervical cytology. Issue 5 (21st February 2018) - Lee, Hyekyung; Han, Myungein; Yoo, Taejo; Jung, Chanho; Son, Hyun‐Jin; Cho, Migyung
Abstract : Objectives: Development of computerized image analysis techniques has opened up the possibility for the quantitative analysis of nuclear chromatin in pathology. We hypothesized that the features extracted from digital images could be used to determine specific cytomorphological findings for nuclear chromatin that may be applicable for establishing a medical diagnosis. Methods: Three parameters were evaluated from nuclear chromatin images obtained from the liquid‐based cervical cytology samples of patients with biopsy‐proven high‐grade squamous intraepithelial lesion (HGSIL), and compared between non‐neoplastic squamous epithelia and dysplastic epithelia groups: (1) standard deviation (SD) of the grayscale intensity; (2) difference between the maximum and minimum grayscale intensity (M‐M); and (3) thresholded area percentage. Each parameter was evaluated at the mean, mean‐1SD, and mean‐2SD thresholding intensity levels. Results: Between the mean and mean‐1SD levels, the thresholded nuclear chromatin pattern was most similar to the chromatin granularity of the unthresholded grayscale images. The SD of the gray intensity and the thresholded area percentage differed significantly between the non‐neoplastic squamous epithelia and dysplastic epithelia of HGSIL images at all three thresholding intensity levels (mean, mean‐1SD, and mean‐2SD). However, the M‐M significantly differed between the two sample types for only two of the thresholding intensity levels (mean‐1SD and mean‐2SD). Conclusions: The digital parameters SD and M‐M of the grayscale intensity, along with the thresholded area percentage could be useful in automated cytological evaluations. Further studies are needed to identify more valuable parameters for clinical application.